PENGEMBANGAN WEBSITE PROGRAM STUDI DALAM UPAYA PENINGKATAN PELAYANAN AKADEMIK MAHASISWA PENDIDIKAN TEKNIK MESIN UNIVERSITAS SARJANAWIYATA TAMANSISWA - Setuju Setuju (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2016)
This research aims to develop a website product for the Mechanical Engineering Education Department that is suitable for academic service. It is very important to do in order to improve the service quality of the Mechanical Engineering Education Department to realize its vision and mission and also to give beneficial effect in improving the accreditation status of the department. The design of this research is Research and Development of 4D model. The steps of 4D model includes: define, design, develop, and disseminate. The define step aims to collect various information related to the product to develop. The design step aims to prepare the design of first product. The develop step aims to produce a suitable website. The disseminate step is the last step in developing the product. The subject of this research consisted of two parties; they are validator (website experts) who validated the website and students of the Mechanical Engineering Education Department of Sarjanawiyata Tamansiswa University. The instruments used to collect the research data are validation sheet of the suitability of website product and questionnaire for student satisfaction of academic service. The data analysis used descriptive quantitative and qualitative techniques. The Website of the Mechanical Engineering Education Department that has been developed is in good category, so it has been suitable for public access. The website can be accessed through: http://ptm.ustjogja.ac.id. The website gives students academic service satisfaction in a very good category.